Pendampingan Pemanfaatan Digital Marketing pada UMKM di Desa Pandanmulyo, Kecamatan Tajinan, Kabupaten Malang - Priska Choirina; Farid Wahyudi; Urnika Mudhifatul Jannah; Pangestuti Prima Darajat (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The community service partners in this activity are Usaha Mikro Kecil dan menengah (UMKM) operating in the food sector, handicrafts to tourism managers in Pandanmulyo Village, Tajinan District, Malang Regency. Currently, UMKM, only market their products and promote tourist destinations in a limited environment, such as through the Pandanmulyo Village website and through word of mouth, so the information is not widely disseminated. Therefore, these UMKM require training on the importance of utilizing digital marketing so that their marketing system can be improved and can reach more target markets and support a better increase in sales. In addition, UMKM were given training in creating Instagram and Shopee accounts, as well as guidance on managing these platforms efficiently. Based on the results of this activity, it is recommended to continue the use of digital marketing strategies and provide regular mentoring so that the marketing and sales of UMKM products and tourism promotion can be improved effectively and optimally.